Confined Metastable 2‐Line Ferrihydrite for Affordable Point‐of‐Use Arsenic‐Free Drinking Water. Issue 7 (5th December 2016) - Kumar, Avula Anil; Som, Anirban; Longo, Paolo; Sudhakar, Chennu; Bhuin, Radha Gobinda; Gupta, Soujit Sen; Anshup,; Sankar, Mohan Udhaya; Chaudhary, Amrita; Kumar, Ramesh; Pradeep, Thalappil
Abstract : Arsenic‐free drinking water, independent of electrical power and piped water supply, is possible only through advanced and affordable materials with large uptake capacities. Confined metastable 2‐line ferrihydrite, stable at ambient temperature, shows continuous arsenic uptake in the presence of other complex species in natural drinking water and an affordable water‐purification device is made using the same.